The genetic structure of SARS‐CoV‐2 does not rule out a laboratory origin: SARS‐COV‐2 chimeric structure and furin cleavage site might be the result of genetic manipulation - Segreto, Rossana; Deigin, Yuri (BioEssays, 2021)
Severe acute respiratory syndrome‐coronavirus (SARS‐CoV)‐2′s origin is still controversial. Genomic analyses show SARS‐CoV‐2 likely to be chimeric, most of its sequence closest to bat CoV RaTG13, whereas its receptor binding domain (RBD) is almost identical to that of a pangolin CoV. Chimeric viruses can arise via natural recombination or human intervention. The furin cleavage site in the spike protein of SARS‐CoV‐2 confers to the virus the ability to cross species and tissue barriers, but was previously unseen in other SARS‐like CoVs. Might genetic manipulations have been performed in order to evaluate pangolins as possible intermediate hosts for bat‐derived CoVs that were originally unable to bind to human receptors? Both cleavage site and specific RBD could result from site‐directed mutagenesis, a procedure that does not leave a trace. Considering the devastating impact of SARS‐CoV‐2 and importance of preventing future pandemics, researchers have a responsibility to carry out a thorough analysis of all possible SARS‐CoV‐2 origins.